Corporate and global standardization initiatives in contemporary society - Jakobs, Kai 1957- (Advances in human and social aspects of technology (AHSAT) book series, 2018)
"This book contains the latest research related to standards and standardization in organizations of all types and society at large. It also advances knowledge relating to standards and standardization for diverse settings and applications"--